Skin diseases in Turkish soldiers - Sezai Sasmaz; Mustafa Celik (Wolters Kluwer Medknow Publications, 2011)
This study aimed to determine the prevalence of skin diseases among soldiers who were assigned duties in Kahramanmaras, a province of east Mediterranean region of Turkey. One hundred eighty-eight soldiers were assessed for skin diseases by a complete dermatological examination and the findings were recorded to a form. Apart from the low number of older ones, the soldiers were of 20-22 years. The diagnosis of superficial fungal infections was made by the use of potassium hydroxide preparations in addition to clinical appearance. On completion of the study period, the data were evaluated, and patients were grouped. Pitted keratolysis was the primary dermatologic disease in 34.5% of the soldiers, 29.2% were diagnosed with oral candidiasis, and 25.5% suffered from tinea pedis. Among the soldiers suffering from a cutaneous disease, dyshidrotic eczema (18.6%), intertrigo (excluding candidal intertrigo) (17%), acne (17%), seborrheic dermatitis (14.9%), plantar hyperkeratosis (14.3%), contact dermatitis (13.8%), and folliculitis (12.2%) were the other most frequent dermatoses. Other less frequent dermatoses were asteatotic eczema, callus, onychomycosis, traumatic onychodystrophy, and so on. We conclude that the prevalence of skin diseases in soldiers is very high and is one of the major public health problems that have a significant burden on our nation.